THE REPRESENTATION OF RUSSIA IN THE WORK BY I.A. BUNIN - Marina A. Kulabukhova , Victor P. Rimsky, Olga N. Rimskaya (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article reveals the prerequisites for the emergence and explains the meaning of the collective vision of Russia in the Patriotic-oriented works by I. A. Bunin. In the context of a comprehensive approach to I. A. Bunin’s heritage, the semantic relationship of literary texts as the results of literary and philosophical, aesthetic, and spiritual and moral searches of the author is explained. The tragedy of personal fate and fate in general, which manifests itself in the strengthening of the motif of lost Russia in the literary world of I. A. Bunin, also predetermines a special role of I. A. Bunin as a point man of thoughts and feelings of Russian emigration of the first wave and the return to the timeless spiritual values of Russian culture.